2008
DOI: 10.1097/wco.0b013e32830efdc2
|View full text |Cite
|
Sign up to set email alerts
|

Limb–girdle muscular dystrophies

Abstract: The increased understanding of the genes and pathogenic mechanism of the LGMDs will improve diagnostic processes and prognostic accuracy, and promote therapeutic strategies. European and global LGMD patient registries will increase current knowledge on natural history and facilitate translational research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 70 publications
1
67
0
4
Order By: Relevance
“…Immunostaining performed on muscle biopsy and genetic analysis can define the diagnosis of the LGMD subtypes. 52 In a recent analysis conducted in a large sample of genetically diagnosed LGMD Italian patients, CAV3 mutations represented the 5% of the probands. 53 The first description of an LGMD associated with Cav-3 deficiency was by Minetti et al 54 who reported affected individuals in two unrelated Italian families.…”
Section: Caveolin-3 and Muscle Diseasesmentioning
confidence: 99%
“…Immunostaining performed on muscle biopsy and genetic analysis can define the diagnosis of the LGMD subtypes. 52 In a recent analysis conducted in a large sample of genetically diagnosed LGMD Italian patients, CAV3 mutations represented the 5% of the probands. 53 The first description of an LGMD associated with Cav-3 deficiency was by Minetti et al 54 who reported affected individuals in two unrelated Italian families.…”
Section: Caveolin-3 and Muscle Diseasesmentioning
confidence: 99%
“…An important group of muscular dystrophies is limb-girdle muscular dystrophies, which predominantly present with proximal weakness with sparing of the facial and distal muscles, and cardiomyopathy in some subtypes [2]; however even when the disease begins with limb-girdle weakness, additional clinical features lead to consider other myopathic disorders. When limb-girdle weakness is combined with early distal muscle involvement, contractures and cardiac involvement, the phenotype is usually categorized as Emery-Dreifuss muscular dystrophy (EDMD) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…11,20 Variable expressivity was observed in term of age at onset and muscular symptoms. With few exceptions, the adult patients showed the 'canonical' clinical features of LGMD, characterised by slowly progressive proximal muscle weakness in upper and lower limbs, with onset during the fifth decade of life and a relatively benign course.…”
Section: Discussionmentioning
confidence: 99%